Modal Kerja CV. Percetakan Sofasco - Nur Aeni, Naura; Azzahra Oktaviani, Tia; Pertiwi Hari Sandi, Santi; Epty Hidayaty, Dwi (Jurnal Etnik: Ekonomi-Teknik, 2023)
The purpose of this study is to determine the working capital on the CV. Sofasco Printing. The method used is descriptive such as literature studies, interviews and document analysis. Running a business requires working capital for its daily operations. Of course, every job in the business requires sufficient and good working capital. The company does not experience difficulties facing economic crises or financial problems, thus enabling the company to operate properly and optimally and achieve company goals. CV income. Sofasco printing per month can be seen from January to August, while for seasonal increases there are from June to August where there are many purchases such as Indonesian Independence Day, invitation cards and so on. Industrial visits that experience an increase in working capital can provide varying results depending on the industrial sector and the strategies implemented. The following are some of the possible outcomes as a result of increasing working capital in industrial visits: Increased Production, Improved Production Quality, Improved Operational Efficiency, Improved Marketing and Sales, Increased Profits and Growth of the company.